ANALISIS KEMAMPUAN REPRESENTASI MATEMATIS MAHASISWA PADA MATA KULIAH PROGRAM LINEAR - Erma Monariska; Elsa Komala (Department of Mathematics Education, Universitas Kuningan, 2021)
This article aims to find out how the mathematical representation abilities and difficulties experienced by students in solving problems in the Linear Program course. The research method uses descriptive quantitative methods. Subjects in this study were students of level III Mathematics Education Study Program, University of Suryakancana, data collection was carried out using test instruments in the form of descriptive questions related to mathematical representation abilities. The results of this study are: 1) Students have a fairly good mathematical representation ability and are classified as moderate in the linear program course but are still weak in indicators of the ability to represent mathematical expressions (making mathematical equations or models, solving problems involving mathematical expressions). This is because students are not familiar with story questions and non-routine questions and mathematical representation questions; 2) Students experience difficulties in designing, compiling, formulating and constructing mathematical models correctly, determining the feasible area (solution area) as well as the solution point of the given problem, as well as carelessness and lack of student care in calculating and completing the iteration process and forgetting to determine variables entry and exit so that it has an impact on the work results / improper solutions of the problems presented.